A pre-merger stage galaxy cluster: Abell 3733 - Kaya, H. Ilker; Caglar, Turgay; Sert, Hakan (OXFORD UNIV PRESS, 2019)
The galaxy cluster Abell 3733 (A3733) is a very suitable candidate in addressing dynamical processes throughout galaxy cluster mergers. This study shows structural analysis results of A3733 (z = 0.038) based on X-ray and optical data. According to X-ray luminosity map, A3733 hosts two sub-structures separated in the sky by 0.25 Mpc, and the two distinct clumps are located in the East (A3733E) and the West (A3733W) directions. Both sub-structures are centred on two different brightest cluster galaxies (BCGs), and the X-ray and optical centroids of both BCGs substantially coincide with each other. The intraclustermedium (ICM) temperatures of the sub-structures are estimated to be 2.79 keV for A3733E and 3.28 keV for A3733W. Both sub-structures are found to be hosting cool central gas (kT similar to 1.5-2.5 keV) surrounded by hotter gas (kT similar to 3.0-3.5 keV). Besides, the X-ray concentration parameters are found to be c similar to 0.3 for each sub-structure. These results indicate the existence of cool centres for both sub-structures. The optical density map reveals a crowded galaxy population within the vicinity of A3733W. The high probable (per cent 88.2) dynamical binding model of A3733 suggests that the cores of sub-structures have a 3D separation of 0.27 Mpc and will collide in 0.14 Gyr with the relative in-falling velocity of 1936 km s(-1). As a conclusion, this study demonstrates some evidence suggesting that the A3733 system is in the pre-merger state.
Keywords: galaxies: clusters: general; galaxies: clusters: individual: Abell 3733; galaxies: clusters: intracluster medium; X-rays: galaxies: clusters; RADIO-SOURCES; X-RAYS; KINEMATICS; REDSHIFTS; CATALOG; PLASMA; SHOCKS; GAS; APM; Astronomy & Astrophysics